Controlling the Gate: The Functions of the Cytoskeleton in Stomatal Movement - Li, Yihao; Zhang, Xin; Zhang, Yi; Ren, Haiyun (Frontiers in Plant Science, 2022)
Stomata are specialized epidermal structures composed of two guard cells and are involved in gas and water exchange between plants and the environment and pathogen entry into the plant interior. Stomatal movement is a response to many internal and external stimuli to increase adaptability to environmental change. The cytoskeleton, including actin filaments and microtubules, is highly dynamic in guard cells during stomatal movement, and the destruction of the cytoskeleton interferes with stomatal movement. In this review, we discuss recent progress on the organization and dynamics of actin filaments and microtubule network in guard cells, and we pay special attention to cytoskeletal-associated protein-mediated cytoskeletal rearrangements during stomatal movement. We also discuss the potential mechanisms of stomatal movement in relation to the cytoskeleton and attempt to provide a foundation for further research in this field.